Island microgrid power control system based on adaptive virtual impedance - Su, Hongsheng; Zhang, Zhiqiang; Wang, Shaohua (Frontiers in Energy Research, 2023)
When the microgrid is in the islanding operation mode, affected by the line impedance difference between the distributed power sources (DGs), the traditional droop control strategy will lead to the fact that the reactive power of the system cannot be reasonably distributed according to the droop gain, which makes the power grid prone to failure. To solve this problem, an improved sag control strategy based on adaptive virtual impedance is proposed in this paper. The central controller calculates the given power according to the capacity of each inverter and the total load capacity of the line, and then sends it to each inverter, and the inverter determines the value range of the virtual impedance according to the given reactive power. A voltage compensation link is added to the control strategy to compensate for the voltage drop difference caused by the line impedance difference, thereby ensuring the stability of the output power and realizing the power control of the microgrid. The MATLAB/Simulink simulation platform was built to establish the microgrid simulation model in island mode. The simulation results show that when the inverters with the same capacity are connected in parallel, the output active power is the most stable, and the reactive power maintains an equalized state; When inverters of different capacities are connected in parallel, the output active power takes the shortest time to stabilize, and the reactive power basically matches the rated capacity ratio. Therefore, it is fully demonstrated that this method has a good control effect on the power control and operation of the islanded microgrid.